Escherichia coli O157:H7 in Retail Lettuce (Lactuca sativa) in Addis Ababa City: Magnitude of Contamination and Antimicrobial Susceptibility Pattern - Haile, Aklilu Feleke; Alonso, Silvia; Berhe, Nega; Bekele Atoma, Tizeta; Boyaka, Prosper N.; Grace, Delia (Frontiers in Microbiology, 2021)
Escherichia coli O157:H7 is an important foodborne pathogen but largely under investigated in Africa. The objectives of this study were to estimate the prevalence and pattern of antimicrobial resistance of E. coli O157:H7 in lettuce in Addis Ababa, Ethiopia. A total of 390 retail lettuce samples were collected across the 10 subcities of Addis Ababa. E. coli O157:H7 was isolated and identified following ISO-16654:2001 standard. The isolates were further tested for antimicrobial susceptibility to 13 antimicrobials using the Kirby–Bauer disk diffusion method. Out of the 390 lettuce samples examined, two (0.51%) carried E. coli O157:H7. The antimicrobial susceptibility pattern of strains showed resistance to ampicillin (100%) and tetracycline (50.0%). One of the two isolates was multidrug resistant to two antimicrobials tested. The results of this study demonstrate the presence of drug-resistant E. coli O157:H7 in lettuce in markets in Addis Ababa. Despite the low prevalence, its presence in a product that is eaten raw highlights potential public health risk in the area associated with this pathogen.